2014
DOI: 10.1177/0883073814560629
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Magnetic Resonance Imaging (MRI) Analysis of the Developmental Changes of Tourette Syndrome Reveal Reduced Diffusion in the Cortico-Striato-Thalamo-Cortical Pathways

Abstract: There is evidence that cortico-striato-thalamo-cortical pathways are involved in Tourette syndrome. We performed a longitudinal imaging study in 22 patients and 21 healthy controls in order to examine the development of tics and its correlation with magnetic resonance imaging (MRI) findings. Patients were divided in a group with persisting and a group with remission of tics. We found a decrease in volume of left putamen in controls, but not in patients. We found changes in mean diffusivity between patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…In this conception, TS and comorbidities are considered diseases deriving from a failure in the mechanisms responsible for sensory and motor gating (19). In support of the role of BG dysfunction in TS, a recent diffusion-weighted imaging study confirmed that delayed or altered development in the CSTC networks is a possible factor leading to TS manifestations and its normalization is associated with remission of tics (20). …”
Section: Introductionmentioning
confidence: 88%
“…In this conception, TS and comorbidities are considered diseases deriving from a failure in the mechanisms responsible for sensory and motor gating (19). In support of the role of BG dysfunction in TS, a recent diffusion-weighted imaging study confirmed that delayed or altered development in the CSTC networks is a possible factor leading to TS manifestations and its normalization is associated with remission of tics (20). …”
Section: Introductionmentioning
confidence: 88%
“…Implicating thalamic dysfunction in AN adds to the growing literature suggesting CSTC loop dysfunction as an endophenotype of several disease states, including schizophrenia, ADHD, obsessive-compulsive disorder, and Tourette syndrome (Debes et al, 2014;Mitelman et al, 2005;Nigg and Casey, 2005;Posner et al, 2014a, b). Since alterations in thalamo-frontal connectivity might indicate general CSTC loop dysfunction, future studies could investigate whether other components of CTSC circuitry show alterations in AN.…”
Section: Discussionmentioning
confidence: 99%
“…The adults included in cross-sectional studies who still have symptoms might represent another phenotypic variant of TS with another pathophysiologic mechanism compared with patients with remission of symptoms. 80 To our knowledge, there has been only one longitudinal neuroimaging study on TS. 80 A longitudinal study gives the opportunity to investigate the changes over time in the same patients from childhood into adulthood, and it can help examine the development of tics and comorbidity and correlate these to the neuroimaging findings.…”
mentioning
confidence: 99%
“…80 To our knowledge, there has been only one longitudinal neuroimaging study on TS. 80 A longitudinal study gives the opportunity to investigate the changes over time in the same patients from childhood into adulthood, and it can help examine the development of tics and comorbidity and correlate these to the neuroimaging findings. More longitudinal studies are warranted in the future in order to further examine the pathophysiological mechanisms of TS and the neuroplasticity that might be involved in TS.…”
mentioning
confidence: 99%